In Vitro Propagation Of Chinar (Platanus Orientalis L.) Using Node And Internode Explants (Applied Biological Research, 2017)
The aim of present study was to standardize a micropropagation protocol for  Chinar (Platanus orientalis L.) using nodes and internode segments as explant  materials. The sterilization treatment with 0.1% mercuric chloride for 10 min  showed highest survival percentage in nodal explants (40.2) and internodal  explants (51.9). Internodal explants survivedsterilant treatment better than  nodal explants. For shoot regeneration, MS (Murashige and Skoog medium)  medium supplemented with indole butyric acid (IBA) (0.25 mg L-1), benzyl  adenine (BA) (4 mg L-1) proved best for both nodal and internodal explants.  The maximum number of shoots (9.7 explant-1) greater shoot length (3.9 cm)  was obtained from the internodal explants on MS medium supplemented with  BA (4 mg L-1) + IBA (0.25 mg L-1). MS medium supplemented with IBA (1 mg  L-1) and BA (2 mg L-1) showed 100% rooting percentage as well as highest number and length of roots (15.7 shoot-1, 3.7 cm, respectively). The internodalexplants showed better response than nodal explant. Rooted plantlets were then transferred to perforated plastic pots containing sterilized mixture of sand and soil (1:1) ratio, and grown in greenhouse. The survival percentage after 4 weeks in greenhouse was recorded as 62.3%.
Keywords: Chinar; Platanus orientalis; tissue culture; micropropagation; in vitro propagation